Network Meta-Analysis Comparing Transcatheter, Minimally Invasive, and Conventional Surgical Aortic Valve Replacement - Fong, Khi Yung; Yap, Jonathan J.L.; Chan, Yiong Huak; Ewe, See Hooi; Chao, Victor T.T.; Amanullah, Mohammed Rizwan; Govindasamy, Sivaraj Pillai; Aziz, Zameer Abdul; Tan, Vern Hsen; Ho, Kay Woon (The American journal of cardiology, 2023)
The landscape of aortic valve replacement (AVR) has evolved dramatically over the years, but time-varying outcomes have yet to be comprehensively explored. This study aimed to compare the all-cause mortality among 3 AVR techniques: transcatheter (TAVI), minimally invasive (MIAVR), and conventional AVR (CAVR). An electronic literature search was performed for randomized controlled trials (RCTs) comparing TAVI with CAVR and RCTs or propensity score-matched (PSM) studies comparing MIAVR with CAVR or MIAVR to TAVI. Individual patient data for all-cause mortality were derived from graphical reconstruction of Kaplan-Meier curves. Pairwise comparisons and network meta-analysis were conducted. Sensitivity analyses were performed in the TAVI arm for high risk and low/intermediate risk, as well as patients who underwent transfemoral (TF) TAVI. A total of 27 studies with 16,554 patients were included. In the pairwise comparisons, TAVI showed superior mortality to CAVR until 37.5 months, beyond which there was no significant difference. When restricted to TF TAVI versus CAVR, a consistent mortality benefit favoring TF TAVI was seen (shared frailty hazard ratio [HR] = 0.86, 95% confidence interval [CI] = 0.76 to 0.98, p = 0.024). In the network meta-analysis involving majority PSM data, MIAVR demonstrated significantly lower mortality than TAVI (HR = 0.70, 95% CI = 0.59 to 0.82) and CAVR (HR = 0.69, 95% CI = 0.59 to 0.80); this association remained compared with TF TAVI but with a lower extent of benefit (HR = 0.80, 95% CI = 0.65 to 0.99). In conclusion, the initial short- to medium-term mortality benefit for TAVI over CAVR was attenuated over the longer term. In the subset of patients who underwent TF TAVI, a consistent benefit was found. Among majority PSM data, MIAVR showed improved mortality compared with TAVI and CAVR but less than the TF TAVI subset, which requires validation by robust RCTs. [Display omitted]